The Influence Of Mahfudzat Learning Strategies On The Learning Motivation Of Class IX Students At MTsS At-Tajdid Al-Mujahidin 2 Karang Bahagia - Alghifary, Muhammad Hafidz Wijdan; Achmad Junaedi Sitika (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2024)
MTsS At-Tajdid Al-Mujahidin 2 Karang Bahagia is a form of formal education that has a lot of religious learning such as Al-Quran, Hadist, Aqidah Akhlak, Fiqh and so on. What is interesting is that in this religious study there are many sentences or sayings that contain motivation, whether from Al-Quran, Hadist or the words of scholars from the Mahfudzat. In the learning process, motivation is one of the important things for students. The learning process will be successful when students have motivation to learn. Therefore, educators need to foster students' learning motivation. To obtain optimal learning results, educators are asked to be creative in building and generating students' learning motivation. The ability of educators to determine learning strategies will have an influence on the motivation of students' learning outcomes, especially on students' learning motivation which is embedded in students so that students can demonstrate their learning behavior. In this case, educators apply the mahfudzot learning strategy as an alternative to students' learning motivation. Keywords: Strategy influence, Mahfudzat learning, motivation